From education policy to class practices: Indonesian secondary EFL teachers’ self-efficacy in developing school-based EFL syllabi - Kamil, Dairabi; Mukminin, Amirul; Abu Kassim , Noor Lide (University of Pittsburgh, 2013)
The purpose of this quantitative inquiry was to examine the self-efficacy of Indonesian secondary school English as foreign language (EFL) teachers in developing a school-based EFL syllabus. The data were collected through a survey to 98 secondary school EFL teachers in the District of Kerinci, Jambi Sumatra, Indonesia. The data were analyzed through the Rasch Analysis (Linacre 2004, 2006). The results revealed that the teachers had a high-self efficacy in developing the syllabus. However, they tended to be less efficacious on theoretical tasks in the syllabus development and on tasks that were not part of their responsibility in previous curricula. In addition, this study also produced an instrument for measuring teachers’ self-efficacy in developing the syllabus that can be used for similar purposes in other contexts.